2022
DOI: 10.1021/acs.chemmater.1c03220
|View full text |Cite
|
Sign up to set email alerts
|

Customized Carbon Dots with Predictable Optical Properties Synthesized at Room Temperature Guided by Machine Learning

Abstract: Fluorescent carbon dots (CDs) have been increasingly used in fluorescence detection and imaging based on their tunable fluorescence (FL) and resistance to photobleaching. However, the fast and reliable design of fluorescent CDs with specific optical properties involves a number of factors, such as the concentration of precursors, reaction time, and solvents. Therefore, it is usually considered difficult to design CDs with favorable optical properties. Herein, we report an extreme gradient boosting (XGBoost) mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 45 publications
1
45
0
Order By: Relevance
“…More importantly, machine learning has been used to gain a further understanding and build experimental models using data and algorithms to correlate the structure–property relationship of CDs [ 139 ]. Thus, machine-learning-based techniques have been used to develop strategies that allow the synthesis of CDs with targeted optical properties [ 140 , 141 ], optimized quantum yields [ 142 ] and high selectivity in gas sensing [ 143 ]. Since machine learning is already shedding some light on the structure–property relationship, it is possible that this tool can potentially predict the identity of the CDs (i.e., GQDs, CQDs, CNDs and CPDs) and the type of dimensional carbon formed after heat treatment or catalysis reactions, and potentially can also help control the amount of dopant (e.g., N-, P-doping) in the final carbon structure.…”
Section: Mechanism Of Formation Of the Dimensional Carbon Allotropes ...mentioning
confidence: 99%
“…More importantly, machine learning has been used to gain a further understanding and build experimental models using data and algorithms to correlate the structure–property relationship of CDs [ 139 ]. Thus, machine-learning-based techniques have been used to develop strategies that allow the synthesis of CDs with targeted optical properties [ 140 , 141 ], optimized quantum yields [ 142 ] and high selectivity in gas sensing [ 143 ]. Since machine learning is already shedding some light on the structure–property relationship, it is possible that this tool can potentially predict the identity of the CDs (i.e., GQDs, CQDs, CNDs and CPDs) and the type of dimensional carbon formed after heat treatment or catalysis reactions, and potentially can also help control the amount of dopant (e.g., N-, P-doping) in the final carbon structure.…”
Section: Mechanism Of Formation Of the Dimensional Carbon Allotropes ...mentioning
confidence: 99%
“…Also, while there recently have been successful examples to reduce the full width at half-maximum (FWHM) of their emission band, CDs generally exhibit PL with a rather broad FWHM exceeding 50 nm . CDs have been studied intensely for applications ranging from bioimaging, theranostics, and optoelectronics to catalysis. , In recent years, there have been reports on the optimization of CD design using various machine learning methods in order to rationalize synthesis of CDs with certain required properties. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, machine learning (ML) has been changing the traditional research paradigm in science and technology. Many ML-related studies have been reported on the important role that ML plays in broadening and optimizing the material preparation process, and they have provided parameter correlation information and predicted unique properties. Lee et al adopted the ML method to estimate the optical properties of GNRs based on the statistical characterization of GNR morphologies. Beyond the morphology, unraveling the physical nature of the optical performance of GNRs entails a QC approach.…”
Section: Introductionmentioning
confidence: 99%